Assessment of somatotype in young voleyball players: Validity as criteria to select young sports talents - Luís Carrasco Páez; Borja Sañudo Corrales; Moisés de Hoyo Lora (Universidade Federal de Santa Catarina, 2008)
The anthropometric characteristics of athletes can determine their sporting performance. For this reason, we've defined the somatotype of young volleyball players in order to be able to control their sports training and to ensure their appropriate athletic development. In the present investigation 154 male and female volleyball players (aged from 12 to 14 years) were analyzed. Data were collected according to the ISAK protocol. The results show an endomesomorphic profile for male and female volleyball players agreeing with the predominant profile at these ages. However, after comparing these data with results obtained in other studies, we observed a certain homogeneity in the male somatotype, invalidating the current trend of using this parameter as criteria to select young sports talent. However, somatotype could be a factor to take into account with female athletes, since their profile is much more heterogeneous. ResumoLas características antropométricas de los deportistas pueden determinar su rendimiento deportivo. Por esa razón se pretende conocer el somatotipo de jugadores infantiles de voleibol para poder así, controlar el entrenamiento y asegurar un adecuado desarrollo de los deportistas. En este estudio se analizaron 154 jugadores/as, con edades comprendidas entre 12 y 14 años. Los datos se extrajeron según las técnicas recomendadas por la ISAK (2001). Los resultados mostraron um perfil endomesomorfo tanto en chicos como en chicas, lo que concuerda con el perfil predominante en estas edades. Por otra parte, al comparar el somatotipo de estos jugadores con el de otros estudios observamos una cierta homogeneidad en el caso de los chicos, lo que invalidaría la tendencia actual de usar este parámetro como criterio para la selección de jóvenes talentos deportivos. Sin embargo, si podría ser un elemento a tener en cuenta en el caso de las chicas, ya que su perfil es mucho más heterogéneo.